Microwave synthesis and crystal structures of two cobalt-4,4′- bipyridine-sulfate frameworks constructed from 1-D coordination polymers linked by hydrogen bonding - Timothy J. Prior (2018)
Two extended solids displaying both one-dimensional coordination polymer and two-dimensional hydrogen-bonded structural features has been prepared under microwave-assisted hydrothermal conditions. [Co(H2O)4(4,4′-bipyridine)](4,4′-bipyridineH2) ·2(SO4)·2H2O (1) contains one-dimensional coordination polymer chains of composition [Co(4,4′-bipyridine)(H2O)42+]nthat are linked into a three dimensional framework by hydrogen bonding through uncoordinated sulfate and water. Within this framework is located a twice protonated 4,4′-bipyridine molecule (C10N2H102+) which forms two short N-H⋯O hydrogen bonds and eight further non-classical C-H⋯O interactions. The close approach of guest and framework and the large number of interactions between them suggest the cation is important in templating this phase. [Co2(4,4′-bipyridine)2(SO4)2(H2O)6] ·4(H2O) (2) displays one dimensional chains of cobalt-bipyridine which are sinusoidal in nature. Two sets of these chains run parallel to the crystallographic [2 1 2] and [2̄ 1 2̄] directions. Two-dimensional hydrogen-bonded sheets parallel to the xz plane link these; further hydrogen bonds to uncoordinated water help to form a three-dimensional honeycomb network with the centroids of the six-membered rings aligned parallel to the a-axis. The use of microwave synthesis for framework solids of this type is described and the structures of the frameworks and the interactions responsible for their assembly are discussed. The thermal and spectroscopic behaviour of the two phases are described. © 2010 Published by Elsevier Ltd.